Comparing minimally invasive transforaminal lumbar interbody fusion and posterior lumbar interbody fusion for spondylolisthesis: A STROBE-compliant observational study. Issue 37 (September 2017) - Zhang, Dapeng; Mao, Keya; Qiang, Xiaojun
Abstract : Abstract: Although spondylolisthesis was traditionally treated with posterior lumbar interbody fusion (PLIF), minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) was recently proposed as an alternative treatment for spondylolisthesis. However, no studies have focused on the comparison of these 2 techniques' outcome on spondylolisthesis. The operative reports and perioperative data of patients who underwent single-level primary open PLIF (n = 29) and MIS-TLIF (n = 26) for I/II spondylolisthesis were retrospectively evaluated. Patients' demographics, operative blood loss, hospital length of stay, creatine kinase (CK) level, radiographic fusion, complications, and patient-reported outcomes were evaluated. Radiographic fusion was assessed using the Bridwell grading criteria. Preoperative and postoperative patient-reported outcomes included the visual analog scale (VAS) and Oswestry Disability Index (ODI). Average follow-up was 28 ± 3.6 months (range 24–32 months). Bed rest time, hospital stay, estimated blood loss, and operative time in the MIS-TLIF group were significantly lower than those in the PLIF group ( P  < .05). The 3-month postoperative ODI and VAS in the MIS-TLIF group were significantly better than the PLIF group ( P  < .05). However, at the time of the last follow-up, both groups had similar ODI scores and complication, slip reduction, and spinal fusion rates ( P  > .05). Compared with PLIF, MIS-TLIF for grade I/II spondylolisthesis can achieve similar reduction and fusion results with better short-term quality of life, shorter hospital stays, less estimated blood loss, and shorter operative times.